ANALISIS MANAJEMEN RANTAI PASOK STROBERI DENGAN PENDEKATAN MODEL SUPPLY CHAIN OPERATION REFERENCE (SCOR) PADA AGROWISATA RIZKY STROBERI, KADUDAMPIT, SUKABUMI - Muhammad Hibban Dzikryan; Fadhilul Imdad; Rachel Sagita Bakara; Tasya Nuralifia Putri; Dzakiyyah Lainun Zain (Jurnal Riset Multidisiplin Edukasi, 2025)
This study analyzes the Stroberi supply chain at Rizky Stroberi Agrotourism, Kadudampit Sukabumi, using the SCOR (Plan, Source, Make, Deliver, Return) model. Data was obtained through observation, interviews, and literature. The supply chain involves three main parties, Agrotourism, industrial/institutional consumers, and end consumers. The performance assessment results show an average score of 3.34, which indicates that the supply chain is quite effective and integrated, although improvements are still needed in distribution and product Returnmanagement to improve efficiency and service quality.